Identification of human-infective trypanosomes in animal reservoir of sleeping sickness in Uganda by means of serum-resistance-associated (SRA) gene - Welburn, S.C.; Picozzi, K.; Fèvre, Eric M.; Coleman, P.G.; Odiit, M.; Carrington, M.; Maudlin, I. (Elsevier, 2001)
Background: The expansion of sleeping sickness caused by Trypanosoma brucei rhodesiense (T. rhodesiense) beyond its traditional focus in southeast Uganda, has been linked with large-scale livestock restocking. To assess the risk presented to the human population by domestic livestock, human-infective T. b. rhodesiense must be distinguished from non-human-infective T. b. brucei, since both parasites can be present in cattle. We investigated the use of a simple genetic marker to characterize the parasites collected from cattle in villages within the new sleeping sickness focus in Soroti District, Uganda. Methods: 70 T. brucei sl samples of known human infectivity status collected from human beings and cattle in Tororo District, Uganda, from 1989 to 1991 were screened for the presence of the human serum-resistance-associated (SRA) gene by conventional PCR. In 2000-01, blood samples from 200 randomly selected cattle in 6 villages and 2 markets in Soroti District were screened for T. brucei sl parasites (i.e., both T. b. brucei and T. b. rhodesiense) by PCR; positive samples were screened for the presence of the SRA gene. Findings: The SRA gene was present in all 29 samples from patients with sleeping sickness in Tororo District. Of the 41 samples collected from cattle at the same time, the SRA gene was present in the 8 samples that tested resistant to human serum in vitro, whereas it was absent from all 33 isolates that were sensitive to human serum in vitro. Of the 200 cattle sampled in Soroti District, we estimated that up to 18% (95% CI 12-23) were infected with T. b. rhodesiense. Interpretation: Detection of the SRA gene could provide the basis for a simple diagnostic test to enable targeted control of T. b. rhodesiense in the domestic livestock reservoir, thereby reducing the public health burden of sleeping sickness in east Africa.